PENGARUH SUPERVISI AKADEMIK, KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU DALAM MENGELOLA PEMBELAJARAN DI SEKOLAH - Achmad, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The aim of this research was describe (1) the influence of the academic supervision of the school head teacher Against boarding costs in primary schools in the district of Pontianak City, (2)Â  the influence of the principal effect of situational Leadership Against boarding costs at primary school teachers in the district of Pontianak City, (3) the influence of academic supervision and situational leadership principals simultaneously influential on teacher performance District of Pontianak City Elementary School Teacher. The method used was a survey method with the type of explanatory research. The sample in this study amounted to 171 teachers. Data measurement techniques using a likert scale. The data analysis techniques used are descriptive statistics and inferential statistical of multiple regression. The result showed that : (1) there is the influence of Academic Supervision on teacher performance SDN District of Pontianak City by 57.90 percent; (2) there is the influence of situational leadership to the school head teacher performance SDN District of Pontianak City by 55.10 percent; (3) Academic supervision, Situational Leadership Principal simultaneously to variable performance District of Pontianak City Elementary School Teacher of 53.10 percent, amounting to 53.10 percent. Key word: academic supervision, situational Leadership, teacher performance